2023
DOI: 10.3390/ijms24098448
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Community Survey of Wolbachia-Infected Parthenogenetic Parasitoid Trichogramma pretiosum (Hymenoptera: Trichogrammatidae) Treated with Antibiotics and High Temperature

Abstract: Wolbachia has been shown to induce thelytokous parthenogenesis in Trichogramma species, which have been widely used as biological control agents around the world. Little is known about the changes of bacterial community after restoring arrhenotokous or bisexual reproduction in the T. pretiosum. Here, we investigate the emergence of males of T. pretiosum through curing experiments (antibiotics and high temperature), crossing experiments, and high-throughput 16S ribosomal RNA sequencing (rRNA-seq). The results o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 73 publications
(92 reference statements)
0
1
0
Order By: Relevance
“…The PI strength in Trichogramma wasps is strongly influenced by Wolbachia density in the germ line and eggs. Previous studies showed that weak PI strength is often associated with biotic (e.g., continuous oviposition) or abiotic (e.g., high temperature) factors that can affect the transmission rate of Wolbachia ( Zhou et al., 2022a ; Guo et al., 2023 ). The unstable PI strength of Wolbachia -infected Trichogramma can impact the quality of Trichogramma offspring and their efficacy in pest control.…”
Section: Discussionmentioning
confidence: 99%
“…The PI strength in Trichogramma wasps is strongly influenced by Wolbachia density in the germ line and eggs. Previous studies showed that weak PI strength is often associated with biotic (e.g., continuous oviposition) or abiotic (e.g., high temperature) factors that can affect the transmission rate of Wolbachia ( Zhou et al., 2022a ; Guo et al., 2023 ). The unstable PI strength of Wolbachia -infected Trichogramma can impact the quality of Trichogramma offspring and their efficacy in pest control.…”
Section: Discussionmentioning
confidence: 99%